Mortality and heart failure in patients with severe tricuspid regurgitation. Risk stratification based on TR severity by CMR. (14th October 2021) - Hinojar Baydes, R; Gonzalez-Gomez, A; Garcia-Martin, A; Monteagudo, J M; Alonso-Salinas, G; Hernandez-Jimenez, S; Fernandez-Mendez, M A; Garcia De Vicente, A; Jimenez-Nacher, J J; Zamorano, J L; Fernandez-Golfin, C
Abstract: Background: Tricuspid regurgitation (TR) is related to poor prognosis independently of the etiology. A new scale classification has been proposed to better characterize the grading of more than severe TR. Massive and torrential TR seem to have worse prognosis based on echocardiographic studies. Purpose: To stratify patients' risk based on TR severity by CMR Methods: Consecutive patients in stable clinical condition evaluated in the Heart Valve Clinic with significant TR (severe, massive or torrential TR) with a contemporaneous echo and CMR were included. TR severity was evaluated by vena contracta (VC) and ERO method, using EPIQ system (Phillip Medical system Andover, Massachusets) and by TR regurgitant fraction (TRF) using a 1.5 Tesla CMR Philips scanner. A combined endpoint of hospital admission due to right heart failure and cardiovascular mortality was defined. Results: 75 patients were included in this study (age 75±8 years, 75% female, 91% functional TR). According to echocardiography 75% were severe, 15% were massive and 10% were torrential TR. Patients with massive and torrential TR showed higher RV end-diastolic volume and lower RVEF. A TRF >50% held the best accuracy to define massive / torrential TR. During a median follow-up of 3 years (IQR: 1.4 – 3.9 years), 39% of the patients (n=29) experienced the combined endpoint. After adjusting for age and LVEF in a multivariate Cox proportional model, TRF was independently associated with cardiovascular mortality and heart failure (hazard ratio per 1%=1.05, [1.02–1.08], p<0.001). Patients were stratified in 3 groups according to TR severity. Patients with TRF ≤40% showed the lowest incidence of events and those with TRF ≥50% experienced the worse prognosis (log rank=0.001, figure) Conclusion: Patients with massive/torrential TR are populations at higher risk of heart failure and mortality. Risk stratification strategies may identify the patients who benefit the most of intensive therapeutic treatments and intervention on the tricuspid valve. New classification scheme should be included in CMR grading scales. FUNDunding Acknowledgement: Type of funding sources: None.